2002
DOI: 10.1029/2001jb000527
|View full text |Cite
|
Sign up to set email alerts
|

Processes leading to eclogitization (densification) of subducted and tectonically buried crust

Abstract: [1] The transformation of subducted and tectonically buried crustal rocks to denser eclogite plays a fundamental role in the dynamics of mountain building and crustal recycling. However, a complex of partially eclogitized granulites on the island of Holsnøy in the western part of the Norwegian Caledonides reveals that such densification depends in part on the antecedent history of rock masses and that large bodies of untransformed rock can persist metastably even after long residence times in the lower crust. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 63 publications
3
65
0
Order By: Relevance
“…Obviously the granulite-to-eclogite reaction progress is limited by the availability of hydrous fluid. In absence of fluid as a reactant, the granulite is metastably preserved, an inference that can be generalized (e.g., Bjørnerud et al 2002). Field evidence shows that local amphibolitization postdates the partial eclogitization (e.g., Fig. 2c-e; Andersen et al 1991a, Schneider et al 2006, and that amphibolitization is similarly fluid-limited.…”
Section: Field Aspects Of Metamorphismmentioning
confidence: 95%
See 1 more Smart Citation
“…Obviously the granulite-to-eclogite reaction progress is limited by the availability of hydrous fluid. In absence of fluid as a reactant, the granulite is metastably preserved, an inference that can be generalized (e.g., Bjørnerud et al 2002). Field evidence shows that local amphibolitization postdates the partial eclogitization (e.g., Fig. 2c-e; Andersen et al 1991a, Schneider et al 2006, and that amphibolitization is similarly fluid-limited.…”
Section: Field Aspects Of Metamorphismmentioning
confidence: 95%
“…Instead, Sr-isotopic equilibrium is much better compatible with a scenario of pulses of brittle hydraulic fracturing (cf. ), a process that may be related to subduction seismicity (Austrheim and Boundy 1994, Austrheim et al 1997, Bjørnerud et al 2002. This may have been followed by more static, local reactive fluid infiltration into the wallrock, which would easily facilitate isotopic equilibration between fluids and reactive rock.…”
Section: Rb-sr Data: Implications For Eclogite Facies Fluid-rock Intementioning
confidence: 99%
“…A similar lack of water -rock interaction is very rare in terrestrial rocks. Even rocks that are considered 'dry', such as eclogites, owe their recrystallization at the metamorphic peak to the availability of water (Bjørnerud et al 2002;Schneider et al 2007). The isotope systematics of eclogites are accordingly controlled by precisely those rare fluid circulation events (Glodny et al 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, work on high P/T metamorphism has suggested that sudden metamorphism of otherwise metastable rocks can be triggered by episodic fluid fluxing (e.g. Kühn et al 2000;Bjørnerud et al 2002;John et al 2004;Bjørnerud & Austrheim 2006;Glodny et al 2008). Diffusion geospeedometry has typically been performed under the assumption that metamorphism is driven solely by heating, with the influence of P and fluid activity ignored.…”
Section: Alternative Metamorphic Driversmentioning
confidence: 99%
“…This need not always be the case; metamorphism may also be driven by P fluctuations (e. g. García-Casco et al 2002;Forster & Lister 2005;Beltrando et al 2007;Kabir & Takasu 2010;Rubatto et al 2011;Lister & Forster 2016) and/or fluid fluxing (e.g. Bjørnerud et al 2002;John et al 2004;Bjørnerud & Austrheim 2006). Alternative metamorphic drivers and implications for large-scale, extremely short-duration metamorphism are briefly discussed later in this review.)…”
mentioning
confidence: 99%